The Spitzer microlensing program as a probe for globular cluster planets: analysis of OGLE-2015-BLG-0448 - Poleski, Radosław; Tsapras, Yiannis; Wambsganß, Joachim; Schmidt, Robert W. (The astrophysical journal, 2016)
The microlensing event OGLE-2015-BLG-0448 was observed by Spitzer and lay within the tidal radius of the globular cluster NGC 6558. The event had moderate magnification and was intensively observed, hence it had the potential to probe the distribution of planets in globular clusters. We measure the proper motion of NGC 6558 ( ##IMG## [http://ej.iop.org/images/0004-637X/823/1/63/apj523367ieqn1.gif] $\boldsymbolμ _\mathrmcl(N,E)=(+0.36± 0.10,+1.42± 0.10)\;\rmmas\;\rmyr^-1$ ) as well as the source and show that the lens is not a cluster member. Even though this particular event does not probe the distribution of planets in globular clusters, other potential cluster lens events can be verified using our methodology. Additionally, we find that microlens parallax measured using Optical Gravitational Lens Experiment (OGLE) photometry is consistent with the value found based on the light curve displacement between the Earth and Spitzer .